Design contexts in interior space design (sewing workshops as a model) (Al-Academy, 2023)
The topic of context is one of the important topics, which was mentioned as a concept in several fields and different fields, and there were many points of view that defined that concept.He specified the title of the research (design contexts in the design of the interior space), as the research sought to identify the concept of context in the interior design of the spaces of sewing workshops. The research was divided into four chapters:The first chapter, which consists of the methodological framework, the problem of research and the need for it, the importance of research, the goal and limits of research for sewing workshops for vocational schools from (2020-2021).The second chapter: consists of previous studies and the theoretical framework of two topics:The first topic: the concept of context in interior design.The second topic: spaces for sewing workshops.The third chapter: It consists of research procedures, and it is the research community. The descriptive approach was adopted in the sample analysis, which is considered one of the important research methods, in order to study phenomena, improve them, and solve problems. It diagnoses the phenomenon accurately to analyze the information and being the most appropriate with the direction of the research. At the end of the chapter, several results were produced according to the analysis form and the indicators of the theoretical framework.The fourth chapter: includes the results, conclusions, recommendations and proposals reached from this research, the most important of which are:1- A context is one of the main foundations for achieving meaning through simultaneous and sequential elements.2- Poor proportionality in the scale of the space led to poor perception and assimilation of the components of the internal space